Acoustic source tracking algorithm using track before detect - Jiang-an DAI; Tian-shuang QIU (Tongxin xuebao)
In order to improve tracking performance in a noisy and reverberant environment,an acoustic source tracking algorithm using track before detect was proposed.This algorithm used a modified steered response power as localization function which take into account a rectangular region to achieve more robust source location estimation than steered response power function and applied track-before-detect technology to avoid reduplicate calculation of the same rectangular region so that the algorithm could reduce the computation burden without decreasing the accuracy.The simulation results verified that the proposed algorithm can achieve more accurate tracking results than traditional tracking algorithm in a noisy and reverberant environment.